2021
DOI: 10.1002/fsn3.2429
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chitosan coating containing Nepeta pogonosperma extract on shelf life of chicken fillets during chilled storage

Abstract: Chicken is the cheapest and most accessible source of meat. Unlike beef or pork, there are no religious or cultural restrictions on chicken consumption that have made chicken meat a high consumption in the world (Ozunlu et al., 2018). Digestible proteins (low in collagen): unsaturated fats, B-group vitamins (thiamin, vitamin B 6, and pantothenic acid) and minerals such as iron, copper, and zinc make chicken meat a valuable food. The high protein and moisture content of chicken meat provides a good medium for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 56 publications
4
10
0
Order By: Relevance
“…Moreover, the reduction of TVB−N level in beef sample wrapped with CS−based composite film can be related to the favorable antibacterial potential of BITC−α−CD, as we demonstrated in Table 2 . Recently, Afshar Mehrabi et al [ 75 ] also reported a retard increase of TVB−N level for CS film enriched with Nepeta pogonosperma extract packaged chicken meats during 4 °C storage and interpreted this phenomenon as the antibacterial property of the bioactive extract. Furthermore, the increment of the TVB−N value was also reported to be in good connection with the accelerated oxidation in beef samples [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the reduction of TVB−N level in beef sample wrapped with CS−based composite film can be related to the favorable antibacterial potential of BITC−α−CD, as we demonstrated in Table 2 . Recently, Afshar Mehrabi et al [ 75 ] also reported a retard increase of TVB−N level for CS film enriched with Nepeta pogonosperma extract packaged chicken meats during 4 °C storage and interpreted this phenomenon as the antibacterial property of the bioactive extract. Furthermore, the increment of the TVB−N value was also reported to be in good connection with the accelerated oxidation in beef samples [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…When the addition of OLE reached 0.24% and 0.32%, the samples' pH values did not significantly change from the original value after 12 days of storage. There are reports confirming that the combination of CS and Nepeta pogonosperma extract could significantly reduce the pH growth rate of chicken fillets during storage (Afshar Mehrabi et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, lower antiradical potential (higher IC 50 ) was reported for Nepeta extracts. For example, the IC 50 value for Nepeta cataria methanol extract was 171.98 μg ml −1 (Afshar Mehrabi et al, 2021 ). Phenolic compounds are known as the main antioxidant and antiradical agents due to their hydrogen atom donation ability (Shahbazi, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nepeta pogonosperma is a new species identified in 1984 (Jamzad & Assadi, 1984;Valimehr et al, 2014). The previous studies reported the chemical composition, antinociceptive, anti-inflammatory, and antioxidant potential of N. pogonosperma (Afshar Mehrabi et al, 2021;Ali et al, 2012;Khalighi-Sigaroodi et al, 2013;Sefidkon & Akbari-Nia, 2003;Valimehr et al, 2015). The bioactivity of Nepeta species may be related to the terpenoid compounds (such as nepetalactones, sesquiterpenes, monoterpenes, and cyclopentanoid iridoid derivatives), phenolics, and flavonoids (Akdeniz et al, 2020;Formisano et al, 2011;Süntar et al, 2018).…”
mentioning
confidence: 99%